The Influence of Leadership Capability, Lecturer Competency, and Lecturer Commitment on The Accountability of Quality Assurance Institutions and Their Impact on Islamic Higher Education Performance - Ahmad Qurtubi (Journal on Education, 2022)
This research objective probes every impact of leadership capability on performance at UIN Maulana Malik Ibrahim Malang, which is reduced by lecturer competence, lecturer commitment, and institutional accountability. The total of interviewees participating in that research was 188. Total interviewees or interviewees are lecturers at UIN Maulana Malik Ibrahim Malang. That research uses a quantitative approach. The data used in that research are primary data collected against the completed questionnaire outcome. The analytical technique used in this research was SEM-PLS analysis using the SmartPLS program. From the outcome of the analysis of that research, it can be concluded that the leadership capability of superiors at UIN Maulana Malik Ibrahim Malang has a significant impact on institutional performance both directly and indirectly through lecturer competence, lecturer commitment, and institutional accountability. Good leadership capabilities will improve lecturer competence, lecturer commitment and institutional accountability which will further support the high performance of the university.